Thành phần hóa học của nấm Hericium erinaceus SH1 - Kiệm và cộng sự, Phan Văn (Vietnam Journal of Chemistry, 2014)
By combined chromatographies, cerebroside B (1), hericenone D (2), ergosterol (3), ergosterol peroxide (4) and β-adenosine (5) were isolated from the dried finished product of the medicinal mushroom Hericium erinaceus SH1. Their structures were determined from the physico-chemical and spectroscopic evidence. This is the first report of 1 from this fungus.